Analysis on Factors Causing Fatigue among Steel Casting Workers at PT X Sidoarjo - Muhammad Amin Jauhari (The Indonesian Journal of Occupational Safety and Health, 2019)
Introduction: Fatigue is a common condition among workers as a protective mechanism to prevent their body from further damage. PT. X Sidoarjo is a company engaged in the manufacture of steel and wire rod. In the steel casting division, the workers experienced some fatigue. The steel casting workers experience a hot work climate since their work area was close to the billet burner furnace. The physical workload of the workers also affected the level of fatigue. Individual factors and sleep quality also affect the level of individual fatigue. The purpose of this research is to analyze the factors associated with fatigue among  steel casting workers at PT. X Sidoarjo. Metods: This research is categorized as analytical observational research using the cross-sectional approach. The population of this study was 43 workers in the steel casting division at PT. X Sidoarjo. The sample of this research was 30 respondents based on simple random sampling method. The independent variables were individual factors, physical workload, work climate, and sleep quality; while the dependent variable was fatigue. Results: The results showed that there was a significant relationship between physical workload, work climate, and sleep quality with fatigue. There was no significant relationship between individual factors and fatigue. Conclusion: This research conclude that  excessive workload, work climate, and poor sleep quality can cause fatigue among  steel casting workers at PT. X Sidoarjo. Keywords: fatigue, personal factors, physical workload, sleep quality, work climate